Benzobicyclon as a Post-Flood Option for Weedy Rice Control. (17th May 2018) - Young, Mason L.; Norsworthy, Jason K.; Scott, Robert C.; Bond, Jason A.; Heiser, James
Abstract: Benzobicyclon will be the first 4-hydroxyphenylpyruvate dioxygenase (HPPD)–inhibiting herbicide available in US rice production pending registration completion. An observation of benzobicyclon controlling weedy rice in two field trials prompted a greenhouse and field evaluation to determine if benzobicyclon would control weedy rice accessions from Arkansas, Mississippi, and southeastern Missouri. A total of 100 accessions were screened in the greenhouse and field. Percentage mortality was determined in the greenhouse, and percentage control was recorded in the field. Benzobicyclon at 371 g ai ha –1 caused at least 80% mortality of 22 accessions in the greenhouse and at least 80% control of 30 accessions in the field. For most accessions, individual plants within the accession varied in response to benzobicyclon. Based on these results, the sensitivity of weedy rice to benzobicyclon varies across accessions collected in the midsouthern United States, and it may provide an additional control option for weedy rice in some fields.